(untitled) - Prentis, Nicola (Thành phố Hồ Chí Minh, 2014)
The book contains twenty units, each one dealing with a different language function. The early units look at how to interact with people in certain situations while later units focus on expressing different feelings and emotions, such as confidence and excitement.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Spoken English,Nói tiếng Anh